Intrinsic factors in pace bowlers: the predisposition to injury and the relationship with performance - Olivier, Benita (My University, 2014)
The significance of this research lies in the fact that it makes a meaningful contribution to the development of comprehensive injury prevention programmes. The studies included in this thesis investigate technique-related intrinsic factors where injury is prevented at the expense of performance as well as intrinsic factors where there is potential for both injury prevention and performance to be simultaneously optimised. The cricket pace bowler is prone to injury due to the high load nature of the pace bowling action involving a complex sequence of forceful actions, consisting of practiced, particular movements. Various injury prevention programmes incorporating extrinsic factors have been studied and implemented previously, however the intrinsic factors associated with both injury and performance in pace bowlers have not yet been investigated sufficiently. In this thesis an overview of the literature includes the review of injuries sustained by pace bowlers, factors associated with injury and performance, and the kinematics of the pace bowling action. Premier league (amateur) cricket pace bowlers were recruited for this study. All pace bowlers were injury free at the start of the season. Details around past injuries as well as incidence of injuries were recorded throughout an eight month cricket season. Performance measures, namely ball release speed and accuracy, were measured during execution of the pace bowling action. Included in this thesis are six original papers. The first five papers investigated the association between intrinsic factors, injury and performance, while the sixth paper described abdominal muscle adaptations in the pace bowler. The first paper (Chapter 2) investigated bowlers’ ability to perform lumbo-pelvic movement control, static and dynamic balance tests at the start and at the end of a cricket season. Lumbo-pelvic movement control tests could not discriminate between bowlers who sustained an injury during the cricket season and bowlers who did not. However, performance in the single leg balance test (SLBT) (p=0.03) and the star excursion balance test (SEBT) (p=0.02) as measured at the start of the season, was better in bowlers who did not sustain an injury during the season. Paper 2 (Chapter 3) investigated lumbar proprioception (as measured by joint position sense) in the neutral lumbar spine position; as well as lumbar positions corresponding to those at front foot placement and ball release of the cricket pace bowling action in relation to previous injury and injury sustained during the cricket season under review. Lumbar reposition error in the sagittal plane (flexion-extension) was between 1.48˚ and 1.82˚ and in the frontal plane (left-right lateral flexion) it was between 0.81˚ and 0.88˚. Lumbar reposition error, as measured in two planes and in three different positions, was associated with self-reported general injuries, injuries sustained during the bowling action and especially, low back injury sustained in the past (p<0.05). From findings indicated in Papers 1, 2 and 3 (Chapters 2, 3 and 4) it can be postulated that if static balance, dynamic balance and lumbar proprioception can be improved in pace bowlers, their risk of lumbar injury may be reduced. Paper 3 and 4 (Chapter 4 and 5) investigated the relationship between kinematic angles as measured in the power phase of the pace bowling action and injury, as well as performance, respectively. In Paper 3 (Chapter 4) a difference was found between lumbar spine lateral flexion positioning (p=0.02) at the start compared to at the end of the season in injured pace bowlers. The range of flexion between front foot placement and ball release at L1 is much greater in the non-injured group than in the injured group as measured at the end of the season (p=0.03). Bowlers who did not sustain an injury during the season displayed a larger degree of absolute flexion at the start of the season than those who sustained an injury (p=0.02). Findings from Paper 4 (Chapter 5) are that the following absolute angles were positively correlated with higher ball release speeds at the start of the season: a more extended knee angle (p=0.037), a larger arm to thorax angle (p<0.0001), larger L1 (p=0.01), T10 (p<0.0001) and T7 (p<0.0001) segmental spinal lateral flexion and more global trunk left rotation (p=0.02). Paper 3 and 4 (Chapter 4 and 5) thus show that low back flexion and lateral flexion, and front knee kinematics, as found in the power phase of the pace bowling action, are associated with and may predict lower quarter injuries and performance outcomes in cricket pace bowlers. The fifth paper (Chapter 6) hypothesised that correlations between front knee angle, knee reposition error, as a measure of proprioception, and ball release speed should be present, however no such correlation could be established. The correlations between joint reposition error in 140˚ of knee extension (r=0.06), 160˚ of knee extension (r=0.30), front foot placement (r=0.22) and ball release (r=0.23) positions were not statistically significant (p>0.05). Furthermore, correlations between knee position error and reproduced knee angles were also not statistically significant (r=-0.35 to r=0.09; p>0.05). It was concluded that static knee joint position sense is not associated with dynamic knee angle during the bowling action, or with ball release speed and that dynamic mechanisms may contribute to knee angles and bowling speeds. The sixth study (Chapter 7) investigated and highlighted the possible muscle adaptations in absolute muscle thickness and activity as a consequence of the asymmetrical bowling action. The absolute thickness of the non-dominant obliquus abdominis internus (OI) was higher than that of the dominant OI at the start (p<0.0001) as well as at the end of the cricket season (p<0.0001). At the start of the season the percentage change during the abdominal drawing in manoeuvre, thus a measure of muscle activity, was higher for the non-dominant OI than for the dominant OI (p=0.02). Absolute thickness of the dominant obliquus abdominis externus (OE) at rest was significantly higher at the end of the season compared with at the start of the season (p<0.0001). During right side active straight leg raise, the activity of the left transversus abdominis (TA) was significantly higher than that of the right TA during left side active straight leg raise (p=0.03) when measured at the end of the season. These asymmetries in abdominal muscle thickness and activity may contribute to the predisposition to low back injury in cricket pace bowlers or may occur in an attempt to protect the pace bowler against injury. In conclusion, the high load nature of the pace bowling action allows for high ball release speeds to be attained but at the same time renders the pace bowler vulnerable to injury. Intrinsic factors found to be associated with both lower quarter injury and performance should be appropriately incorporated into injury prevention programmes in order to prevent the occurrence of injuries in the presence of the high load nature of the pace bowling action. Further research needs to be conducted on the effectiveness of these injury prevention programmes to prevent injury amongst pace bowlers.
Keywords: pace bowlers injuries; cricketers injuries; Sports; Athletics Injuries--prevention & control; Physical Therapy